Hydropower and local community: A case study of the Kamchay dam, a China-funded hydropower project in Cambodia. Issue 3 (27th May 2017) - Pheakdey, Heng
Abstract: To solve its chronic power shortage, the Government of Cambodia has placed the development of hydropower as one of the national priorities. With a total of US2.4bn in investment, China is the most prominent player in hydropower development in Cambodia. The increase of hydropower projects and China's involvement has sparked national controversy. There are contentious debates on such projects despite their potential economic benefits because of the concerns over their social and environmental consequences. Combining site visits and field interviews, this article studies the China-funded Kamchay hydropower project in Cambodia and examines its impact on the local community two years after it began operating. This article makes a distinct contribution to the ongoing debate on the effects of large-scale natural resource investments on sustainable development in Cambodia.